2019
DOI: 10.14744/dajpns.2019.00016
|View full text |Cite
|
Sign up to set email alerts
|

The Difficulties in Emotion Regulation, Separation Anxiety and Impulsivity as Predictors of Women’s Intimate Partner Violence Experiences

Abstract: How to cite this article: Kayha Y, Taskale N. Difficulties in emotion regulation, separation anxiety, and impulsivity as predictors of women's intimate partner violence experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Children with DLD have expressed how their experience of safety and security is highly dependent on who they are with [46], further compounding the wish to stay with a trusted caregiver. Ensuring separation anxieties and emotional dysregulation are not carried into adulthood is important, as neurotypical adults who demonstrate these characteristics are suggested to have an increased risk of developing unhealthy interpersonal relationships [141].…”
Section: The Manifestation Of Anxiety In Children With Dldmentioning
confidence: 99%
“…Children with DLD have expressed how their experience of safety and security is highly dependent on who they are with [46], further compounding the wish to stay with a trusted caregiver. Ensuring separation anxieties and emotional dysregulation are not carried into adulthood is important, as neurotypical adults who demonstrate these characteristics are suggested to have an increased risk of developing unhealthy interpersonal relationships [141].…”
Section: The Manifestation Of Anxiety In Children With Dldmentioning
confidence: 99%
“…In this sense, several authors have shown that difficulties in emotional regulation are a factor that hinders the prevention of violence [ 45 , 46 , 47 , 66 , 67 ]. In addition, it has been pointed out that people who present difficulties in emotional regulation do have greater difficulty in managing their negative emotions in stressful situations, especially among those with insecure attachment styles [ 46 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. These studies are consistent with our findings, which show a high prevalence of insecure attachment styles in subjects with emotional regulation difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…These facts seem to explain the connection found between difficulties in emotional regulation, violence and the presence of insecure attachment styles [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Therefore, this combination of factors could translate into violent responses towards their partners when the aggressors feel that their attachment needs are not satisfied [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this state, they may be more prone to act aggressively or at a higher risk of becoming victims of violence. Kayha and Tasklae have assessed the relationship between difficulties in separation anxiety, emotion regulation, impulsivity, and women's experiences of close partner abuse in females who are married, or in a romantic relationship now or during the previous year [10]. They were asked to conduct online self-report questionnaires, using various scales to assess their demographic, emotion regulation, separation anxiety level, and impulsivity.…”
Section: The Role Of Asad In Conflictmentioning
confidence: 99%